Love songs : a hidden history - Gioia, Ted (Oxford University Press, 2015)
The love song is timeless. From its beginnings, it has been shaped by bohemians and renegades, slaves and oppressed minorities, prostitutes, immigrants and other excluded groups. But what do we really know about the origins of these intimate expressions of the heart? And how have our changing perceptions about topics such as sexuality and gender roles changed our attitudes towards these songs? In Love Songs: The Hidden History, Ted Gioia uncovers the unexplored story of the love song for the first time. Drawing on two decades of research, Gioia presents the full range of love songs, from the f.